Information Needs and Seeking Behaviors of Farmers in Jere Local Government Area, Borno State, Nigeria - Yusuf, Abdurrahman; Baba, Audu Alhaji; Mahmood, Zainab Usman; Badia, Muhammad Zannah-Bukar (Communicate: Journal of Library and Information Science, 2023)
The paper assessed information needs and seeking behavior of farmers inJere Local Government area of Borno State, Nigeria. The objectives of the study are to find out the information needsof farmers in Jere Local Government area of Borno State; information seeking behavior of farmers in Jere Local Government area of Borno State;sources of information farmers use in Jere Local Government area of Borno State andlevel of awareness of information of rural farmers in Jere Local Government area of Borno State,Nigeria.Survey research design was adopted for the study with 136 population drawn from farmers’ association groups.Self-designed questionnaire titled “Assessment of Information Needs and Seeking Behavior of Farmers in Jere Local Government area of Borno StateNigeria (AINASBOFIJBSN) was used. Data allocated were analyzed using descriptive statistics of frequency counts and percentage scores.The findings revealed that majority of information needs of farmers was at high level sought from their colleagues, friends, family and relied on best experience. Based on the findings, it was recommended that government should provide timely information to farmers, and also provide public library service to the farmers foradequately creating awareness among them.